Amplification of Seed Germination and Seedling Growth Attributes of a Multipurpose Tropical Tree Parkia timoriana (DC.) Merr. Through Different Pre-sowing Seed Treatments - MANISH KUMAR SINGH; PAPORI BORPUZARI; ARINDAM DUTTA; NAFEESH AHAMED (Seed Research, 2026)
Parkia timoriana (DC.) Merr. is highly underutilized, multipurpose and sustainably harvested legume tree of north east India. It is mainly propagated through seeds, but due to over exploitation, insect-pest infestation, climatic disruption and various other threats its population is declining from the wild. Further due to innate seed coat dormancy, the germination percentage and seed vigour is very less which further resulted into poor natural regeneration. Keeping this view, we attempted to investigate phenotypically superior trees based on scoring scale from wild and screened out best pre-sowing treatment for enhancing germination and growth attributes. Study started with selection of 21 healthy populations of P. timoriana from northeast India through field survey, assortment of phenotypically superior trees through scoring scale method and tested different pre-sowing treatments viz., Growth regulators, Acid Scarification and Organics for enhancing seed germination and seedling growth attributes. Study observed that, seeds pre-soaked in water for 24 hour, treated with GA3 (100 ppm, 24 hour) or cow dung slurry (1:1) for 12 hour, required less germination time (2-3 days), having higher germination percentage (90-98%), germination energy (76.41-80.43), germination index (15.4-19.5) and required minimum mean germination time (6-7 days) as compare to unprocessed seeds. This study recommends the use of organic treatments i.e. water soaking for 24 hour, Cow dung slurry (1:1) for 12 hour and growth regulator i.e. GA3 100 ppm for 24 hour, for enhancing seed germination and growth attributes in P. timoriana.